Obesity or increased body mass index and the risk of severe outcomes in patients with COVID-19: A protocol for systematic review and meta-analysis. Issue 1 (7th January 2022) - Yang, Yaxian; Wang, Liting; Liu, Jingfang; Fu, Songbo; Zhou, Liyuan; Wang, Yan
Abstract: Background: To assess the effect of obesity or a high body mass index (BMI) on the risk of severe outcomes in patients with coronavirus disease 2019 (COVID-19). Methods: Studies on the relationship between BMI or obesity and COVID-19 since December 2019. The odds ratio (OR) and weighted mean difference (WMD) with their 95% confidence intervals (CIs) were used to assess the effect size. Results: BMI was significantly increased in COVID-19 patients with severe illness (WMD: 1.18; 95% CI: 0.42–1.93), who were admitted to an intensive care unit (ICU) (WMD: 1.46; 95% CI: 0.96–1.97), who required invasive mechanical ventilation (IMV) (WMD: 2.70, 95% CI: 1.05–4.35) and who died (WMD: 0.91, 95% CI: 0.02–1.80). In Western countries, obesity (BMI of ≥30 kg/m 2 ) increased the risk of hospitalization (OR: 2.08; 95% CI: 1.22–3.54), admission to an ICU (OR: 1.54; 95% CI: 1.29–1.84), need for IMV (OR: 1.73, 95% CI: 1.38–2.17), and mortality (OR: 1.43; 95% CI: 1.17–1.74) of patients with COVID-19. In the Asian population, obesity (BMI of ≥28 kg/m 2 ) increased the risk of severe illness (OR: 3.14; 95% CI: 1.83–5.38). Compared with patients with COVID-19 and a BMI of <25 kg/m 2, those with a BMI of 25–30 kg/m 2 and ≥30 kg/m 2 had a higher risk of need for IMV (OR: 2.19, 95% CI: 1.30–3.69 and OR: 3.04; 95% CI: 1.76–5.28, respectively). The risk of ICU admission in patients with COVID-19 and a BMI of ≥30 kg/m 2 was significantly higher than in those with a BMI of 25–30 kg/m 2 (OR: 1.49; 95% CI: 1.00–2.21). Conclusion: As BMI increased, the risks of hospitalization, ICU admission, and need for IMV increased, especially in COVID-19 patients with obesity. Ethics and dissemination: This systematic review and meta-analysis does not require an ethics approval as it does not collect any primary data from patients.